(Z)-N-Methyl-2-(5-methyl-2-oxoindolin-3-ylidene)hydrazinecarbothioamide - Amna Qasem Ali (Acta Crystallographica Section E, 2012)
In the title compound, C11H12N4OS, an intramolecular N—H...O hydrogen bond generates an S(6) ring motif. In the crystal, the molecules form a helical chain along the a axis through an N—H...O hydrogen bond. These chains are extended by an N—H...S hydrogen bond and a C—H...π interaction into a three-dimensional network.